PENGARUH STRUKTUR AKTIVA, PROFITABILITAS, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Dewiayu Wulandari, 11.05.52.0179; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2015)
This study aims to identify and analyze the influence of the structure of assets, profitability, company size, sales growth, and business risk to the capital structure of the manufacturing companies listed in Indonesia Stock Exchange. The sampling method used purposive sampling to study the year 2011 up to 2013. Based on these criteria, obtained a sample of 207 companies. However, in this sample there are outliers that should be excluded from the sample, as many as eleven companies. This, the final number of samples that can be observed as many as 196 companies. Influence the relationship between variables and is described by using multiple linear regression analysis. The results of this study indicate that the asset structure, the size of the company, sales growth, significant positive effect on the capital structure, and profitability of significant negative effect on the capital structure. While the business risk doesnât effect the capital strukture.Keywords: Capital Structure, Asset Structure, Profitability, Company Size, Sales Growth, and Business Risks